Pilot-drill guided vs. full-guided implant insertion in artificial mandibles-a prospective laboratory study in fifth-year dental students - Matthias C. Schulz; Francisca Hofmann; Ursula Range; Günter Lauer; Dominik Haim (SpringerOpen, 2019)
Abstract Background As a growing field in dentistry, the practical education during the undergraduate curriculum in implant dentistry should be extended. Not only the theoretical background but also practical skills are crucial to place implants in patients. In order to determine the exact implant position, several positioning aids are available. In the present laboratory study, the accuracy of implant insertion using two different guiding modes in a group of inexperienced participants was assessed. Methods After three-dimensional planning using the data of a cone beam computed tomography of artificial mandibles, surgical templates were manufactured by thermoforming. In region 35, a sleeve for the pilot drill was used, whereas in region 45, a sleeve allowing a full-guided implant insertion was inserted. Subsequently, a total of 104 implants were placed by 52 undergraduates. Radiographical assessment of the three-dimensional accuracy was performed. Furthermore, the time required to insert the implants was recorded. Statistical analysis followed. Discussion When comparing the three-dimensional accuracy of the virtually planned to the actual inserted implant, a statistically significantly higher accuracy in three-dimensional angulation was achieved for the full-guided (3.388 ± 1.647°) compared to the pilot-drill guided mode (5.792 ± 3.290°). Furthermore, the time required to insert the implant was shorter for the full-guided template (6.23 ± 1.78 min) vs. for the pilot-drill guided (8.84 ± 2.39 min). Both differences reached a statistical significance (p < 0.001). Conclusion Within the limit of this laboratory study, the results suggest that inexperienced surgeons benefit from a full-guided implant insertion. However, the clinical effects have to be discussed as the mismatch was varying in the decimillimeter range.